Pesticides and Cholinesterase - Frederick M. Fishel (EDIS)
PI221, a 4-page fact sheet by Frederick M. Fishel, describes cholinesterase, as well as how several pesticides in different pesticide families can affect cholinesterase levels in humans, and the importance of timely monitoring of cholinesterase levels for any who handle organophosphate or carbamate pesticides, which inhibit cholinesterase. Includes additional sources of information. Published by the UF Department of Agronomy, October 2009.